Peran Evaluasi Diri Guru dalam Supervisi Akademik sebagai Upaya Meningkatkan Inovasi Pembelajaran - Ahmad Jauhari Hamid Ripki; Nurhattati Nurhattati (Universitas Muhammadiyah Mataram, 2025)
Abstract: Self-evaluation plays a strategic role in academic supervision, particularly in fostering improvements in learning quality. In the context of private elementary madrasahs in Karawang Regency, teachers' ability to conduct self-evaluation serves as a vital foundation for developing instructional innovations. This study aims to explore how academic supervision is implemented through teacher self-evaluation as a means to encourage innovation in teaching practices. The concept of innovation in this research refers specifically to teachers’ readiness to reflect on their instructional methods and the extent to which such reflections are applied to enhance the learning process. A qualitative approach was employed using purposive sampling, as participants were selected based on specific characteristics aligned with the study's objectives. Data were collected through in-depth interviews, direct observations, and document analysis. The study was conducted between April and September 2024, involving teachers from the Klari District, Karawang Regency. The findings indicate that self-evaluation has a positive impact on the development of learning innovations. This is evident in the implementation of collaborative strategies, the creative integration of digital media, and the refinement of assessment techniques. The reflective process enables teachers to identify both their strengths and areas for improvement, ultimately contributing to the enhancement of classroom learning quality.Abstrak: Evaluasi diri memiliki peran strategis dalam supervisi akademik, terutama dalam mendorong peningkatan mutu pembelajaran. Di lingkungan Madrasah Ibtidaiyah Swasta Kabupaten Karawang, kemampuan guru dalam melakukan evaluasi diri menjadi landasan penting dalam menciptakan inovasi pembelajaran. Penelitian ini bertujuan untuk mengungkap pelaksanaan supervisi akademik melalui evaluasi diri guru sebagai upaya untuk mendorong pembaruan dalam praktik mengajar. Inovasi yang dimaksud dibatasi pada kesiapan guru dalam merefleksikan praktik pembelajaran serta bagaimana refleksi tersebut diterapkan untuk memperbaiki proses mengajar. Penelitian ini menggunakan pendekatan kualitatif dengan teknik purposive sampling, mengingat karakteristik subjek harus sesuai dengan tujuan studi. Data diperoleh melalui wawancara mendalam, observasi langsung, dan telaah dokumen. Penelitian dilakukan pada April hingga September 2024 dengan partisipan guru-guru dari Kecamatan Klari, Kabupaten Karawang. Hasil kajian menunjukkan bahwa evaluasi diri berkontribusi positif terhadap pengembangan inovasi pembelajaran, yang tampak melalui penerapan strategi kolaboratif, pemanfaatan media digital secara kreatif, serta peningkatan metode asesmen yang beragam. Proses refleksi yang mendalam membantu guru mengenali kekuatan dan area yang perlu ditingkatkan, sehingga berdampak pada perbaikan kualitas proses pembelajaran di kelas.